Panduan Pemeriksaan Analisis Gas Darah Menggunakan Bedside Poct (I‐STAT®) dan Laboratorium Sentral (NOVA PHOX®) dI RSUP Dr. Sardjito - Nurdiansyah, Elba; Pratomo, Bhirowo Yudo; Kurniawaty, Juni (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2021)
Background: Proper postoperative ventilator weaning requires regular monitoring of the patient's blood gas analysis (BGA). Delays in getting the results of the BGA test will be an obstacle in guiding the weaning procedure and affect the length of use of the ventilator. The central laboratory examination (NOVA pHOx®) requires more blood samples, a longer examination time and process compared to POCT which uses fewer blood samples and processes faster results. Methods: This study used a prospective observational design, cohort study, and unpaired comparative analytics. The samples were divided into 2 groups for blood gas analysis i-STAT® and a central laboratory (Nova pHOx®). The inclusion criteria were patients aged 5-60 years who underwent post-open heart surgicaltreatment with a ventilator and a EURO Score <5, The exclusion criteria were patients with ventilator problems, acquired pneumonia, and adult patients with severe chest restriction spirometry. Results: The number of samples was 46 people (POCT: n = 23, Central Laboratory (Nova pHOx®): n = 23).The length of time using the ventilator in the i-STAT group was 1122.8 minutes while the central laboratory group (Nova pHOx®) was 1291.4 minutes with a mean difference of 168.8 minutes but both showed no significant difference with p = 0.303 (p> 0.05). Conclusion: The length of time of using the ventilator in post-cardiac surgery patients with the guidance of blood gas analysis in the i-STAT group and central laboratory (Nova pHOx®). showed no evidence of interaction and no significant effect on the two test modalities